Cochlear Implant Electrode Localization Using an Ultra-High Resolution Scan Mode on Conventional 64-Slice and New Generation 192-Slice Multi-Detector Computed Tomography. Issue 7 (August 2017) - Carlson, Matthew L.; Leng, Shuai; Diehn, Felix E.; Witte, Robert J.; Krecke, Karl N.; Grimes, Josh; Koeller, Kelly K.; Bruesewitz, Michael R.; McCollough, Cynthia H.; Lane, John I.
Abstract : Hypothesis: A new generation 192-slice multi-detector computed tomography (MDCT) clinical scanner provides enhanced image quality and superior electrode localization over conventional MDCT. Background: Currently, accurate and reliable cochlear implant electrode localization using conventional MDCT scanners remains elusive. Methods: Eight fresh-frozen cadaveric temporal bones were implanted with full-length cochlear implant electrodes. Specimens were subsequently scanned with conventional 64-slice and new generation 192-slice MDCT scanners utilizing ultra-high resolution modes. Additionally, all specimens were scanned with micro-CT to provide a reference criterion for electrode position. Images were reconstructed according to routine temporal bone clinical protocols. Three neuroradiologists, blinded to scanner type, reviewed images independently to assess resolution of individual electrodes, scalar localization, and severity of image artifact. Results: Serving as the reference standard, micro-CT identified scalar crossover in one specimen; imaging of all remaining cochleae demonstrated complete scala tympani insertions. The 192-slice MDCT scanner exhibited improved resolution of individual electrodes ( p < 0.01), superior scalar localization ( p < 0.01), and reduced blooming artifact ( p < 0.05), compared with conventional 64-slice MDCT. There was no significant difference between platforms when comparing streak or ring artifact. Conclusion: The new generation 192-slice MDCT scanner offers several notable advantages for cochlear implant imaging compared with conventional MDCT. This technology provides important feedback regarding electrode position and course, which may help in future optimization of surgical technique and electrode design.